Cloning, Expression, and In Silico Analysis of Class IV Poly-(R)-3-hydroxybutyrate Genes from New Strain of Bacillus thuringiensis TH-01 - Zuhdina Sabiqoh; Rukman Hertadi; Enny Ratnaningsih (HAYATI Journal of Biosciences, 2022)
Poly-(R)-3-hydroxybutyrate (PHB) is a bioplastic derivative of polyhydroxyalkanoate (PHA) which can be synthesized by bacteria under certain growth conditions. Previous study has reported a new strain of Bacillus thuringiensis TH-01 isolated from thermite, which found to accumulate PHB. This research aimed to clone PHB biosynthesis genes from B. thuringiensis TH-01 and study its expression as well as predict the tertiary structure of the enzymes. The clone of phaA gene, which encodes PhaA, was obtained as 1182 bp. On the other hand, 2546 bp clone of phaRBC gene cluster was obtained to consist of 744 bp phaB, 1086 bp phaC, and 483 bp phaR, encoding respective PhaB, PhaC, and PhaR proteins. In silico analysis indicated that PhaA, PhaB, PhaC, and PhaR, revealed to have 393, 247, 361, and 160 amino acid, respectively. The predicted model of PhaA, PhaB, and PhaC showed dominant structure of α/β folding motif, while PhaR was dominated by a helix-loop-helix motif. The catalytic residues of PhaA were Cys88, His349, and Cys379, whereas the catalytic residues of PhaB were Ser142, Tyr155, and Lys159. These catalytic residues were identical to those residues obtained in other PHB biosynthetic enzymes reported elsewhere, confirming that our clones were of PHB biosynthetic genes.